Plataforma Robótica de Baixíssimo Custo para Robótica Educacional - Aroca, Rafael Vidal (2012)
Robots are present each time more on several areas of our society, however they are still considered expensive equipments that are restricted to few people. This work con- sists on the development of control techniques and architectures that make possible the construction and programming of low cost robots with low programming and building complexity. One key aspect of the proposed architecture is the use of audio interfaces to control actuators and read sensors, thus allowing the usage of any device that can produce sounds as a control unit of a robot. The work also includes the development of web ba- sed programming environments that allow the usage of computers or mobile phones as control units of the robot, which can be remotely programmed and controlled. The work also includes possible applications of such low cost robotic platform, including mainly its educational usage, which was experimentally validated by teachers and students of seve- ral graduation courses. We also present an analysis of data obtained from interviews done with the students before and after the use of our platform, which confirms its acceptance as a teaching support tool